How do changes in flow magnitude due to hydroelectric power production affect fish abundance and diversity in temperate regions? A systematic review protocol - Meagan Harper; Trina Rytwinski; Jessica J. Taylor; Joseph R. Bennett; Karen E. Smokorowski; Steven J. Cooke (Environmental Evidence, 2020)
Abstract Background Natural flow regimes are an essential component of healthy fluvial systems, but hydropower production alters flow components, disrupting natural processes and impacting species reliant on them. Establishing improved management of flow regimes requires a better understanding of how fish respond to altered flow components, such as flow magnitude. We recently conducted a systematic map to provide a summary of the existing literature base on the impacts of flow regime changes on direct outcomes of freshwater or estuarine fish productivity. Of those studies considering the impacts of flow magnitude changes due to hydropower, studies on fish abundance, biomass and diversity responses were identified as subtopics (i.e., knowledge clusters) that had sufficient coverage for further review. This systematic review proposes to estimate how fish abundance, biomass and diversity are affected by alterations in flow magnitude due to hydropower production. Methods This systematic review will use evidence identified during a systematic map process. An updated English language search will be performed using six bibliographic databases, Google Scholar, and networking tools to include academic and grey literature published after 2016. Eligibility screening will be conducted at two stages: (1) title and abstract, and (2) full-text. We will include all studies that evaluate the impact of changes to (or manipulations of) flow magnitude due to hydropower on fish abundance, density, biomass, yield, species richness, composition or diversity indices. The focus of this review will be on the downstream fluvial effects of flow magnitude changes and include hydroelectric facilities where water moves via gravity or by active pumping. Any freshwater or estuarine fish species or species group in temperate regions will be considered. Included eligible studies will undergo a critical appraisal that will assess the internal study validity. We will extract information on study characteristics, intervention/exposure and comparator details, measured outcomes, and effect modifiers. A narrative synthesis will describe the quantity and characteristics of available evidence, and where sufficient numbers of similar studies are available, meta-analysis will be conducted to estimate an overall mean and variance of effect.